2000
DOI: 10.1007/pl00007262
|View full text |Cite
|
Sign up to set email alerts
|

Primary leiomyosarcoma of the heart subsequent to double carcinomas of the thyroid and lung

Abstract: A 63-year-old woman underwent surgical operations for left lower lung cancer and for thyroid cancer. Nine months later, a third cancer developed in her heart and this tumor was removed by open heart surgery. A pathologic study revealed that the tumor was primary leiomyosarcoma of the heart and thus independent from the previous lung and thyroid carcinomas. This case was regarded as a triple carcinoma including a primary leiomyosarcoma arising from the left atrium. Reports in the literature on primary malignant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Multiple primary malignancies are common only in 3-5% of tumors [ 30 ]. Despite its low incidence, the association of two malignancies in a single patient has been widely reported in the literature, while only a relatively small number (0.5%) of three malignancies have been described including primary cardiac sarcomas [ 30 - 32 ]. Some cases of cardiac sarcomas (pleomorphic spindle cell sarcoma, angiosarcoma) in pacemaker patients are described [ 16 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple primary malignancies are common only in 3-5% of tumors [ 30 ]. Despite its low incidence, the association of two malignancies in a single patient has been widely reported in the literature, while only a relatively small number (0.5%) of three malignancies have been described including primary cardiac sarcomas [ 30 - 32 ]. Some cases of cardiac sarcomas (pleomorphic spindle cell sarcoma, angiosarcoma) in pacemaker patients are described [ 16 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…FABRICIUS et al [9] reported a case of a patient who rapidly developed heart insufficiency owing to leiomyosarcoma of the left atrium. The patient was urgently FUKUOKA et al [10] reported the diagnosis of heart leiomyosarcoma in a patient who had previously been submitted to resection of neoplasms of the thyroid and the lower lobe of the left lung. According to the authors, an anatomicopathological study revealed an independent nature among the histologic types of the three tumours.…”
Section: Discussionmentioning
confidence: 99%
“…As they have a potential of dissemination and local invasion, they can rapidly invade the right ventricle, vena cavas, interventricular septum and the left heart chambers. Alterations of the heart rhythm, arrhythmia and blocks of the conduction of electrical stimuli of the Hiss-Purkinje system are more common in this type of neoplasm than in myxomas and in the metastatic tumours to the heart [8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…The patient was urgently FUKUOKA et al [10] reported the diagnosis of heart leiomyosarcoma in a patient who had previously been submitted to resection of neoplasms of the thyroid and the lower lobe of the left lung. According to the authors, an anatomicopathological study revealed an independent nature among the histologic types of the three tumours.…”
Section: Discussionmentioning
confidence: 99%